The effects of vocational education on adult skills, employment and wages: What can we learn from PIAAC? - Giorgio Brunello; Lorenzo Rocco (SERIEs - Journal of the Spanish Economic Association, 2017)
We have shown that vocational education does not perform as well as academic education both in labour market outcomes and in the level of basic skills, including literacy and numeracy. This is especially true for higher education. Only at the upper secondary or post-secondary level does vocational education perform slightly better than academic education in the probability of being currently employed as well as in the time spent in paid employment, although the differences we find are small.
Keywords: I21; I24; 126; 330; Vocational education; Academic education; PIAAC; Skills; Employment; Wage